(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
Dishonest behavior is common in virtually all cultures. In face of the current Brazilian context and motivated by Ariely´s analysis of the phenomenon, this paper investigates, from a behavior-analytic standpoint, the results obtained with the application of the matrix task in four groups with different contingencies of reinforcement. The present experiment was conducted with 242 participants divided in 4 experimental groups, in a between-subjects design. The results indicate the effect of contextual variables on the frequency of dishonest behavior, not only in the amount of cheating, but also in the number of cheaters. Based on the comprehension of the phenomenon on existing psychological literature about dishonesty, this study put forth a contribution to the behavior analytic interpretation of the phenomenon and points to new variables to be considered for discussion.